Analysis of Problem Solving Ability of First Middle School Students in Learning Science - Castro, Elvira Alicia Mendoza (Integrated Science Education Journal, 2023)
Purpose of the study: The purpose of this study was to analyze the problem-solving abilities of junior high school students in science learning through a literature review. Methodology: The type of research used in this research is qualitative research with a systematic literature review method. The data collection technique used is a literature study. The data analysis technique used is the synthesis matrix Main Findings: Based on the research that has been done, it can be concluded that almost all of the articles analyze the level of students' problem-solving abilities, and most of the articles analyzed use an experimental research design in improving junior high school students' natural science problem-solving skills. Novelty/Originality of this study: The novelty of this research lies in the focus of its research on problem-solving ability analysis, especially in science learning, junior high school research subjects, and using a type of literature review research.